The Troubled World Mandate for Change in the Troubled Campus - Gallagher, Buell G. (Buell Gordon), 1904-; American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
Among the problems facing the United States, the following are most outstanding: (1) the population explosion; (2) pollution; (3) the war in Vietnam; (4) racism and inequality; (5) violence symptomatic of internal disorder; and (6) drug abuse. If institutionalized education wishes to develop human character and to perpetuate social ideals, administrators, educators, and students must unite to propose solutions to these sources of distress. (AF)
Educational level discussed: Higher Education.
ERIC Note: Paper presented at the 25th national conference of the American Association for Higher Education, Chicago, Ill., March 1, 1970.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Responsibility; Higher Education; Social Problems; Social Responsibility